FURTHER STUDIES ON CHANGES IN PROTEIN FRACTION OF FISH MUSCLE DURING STORAGE IN ICE. - DEVADASAN, K; NAIR, M RAJENDRANATHAN (Fishery Technology, 2017)
The changes in the major protein nitrogen fractions of two commercially important fishes of Indian waters, viz., mackerel (Rastrelliger k.anagurta) and lactarius (Lactarius lactarius), during storage in ice are reported. The significance of the findings 1s discussed in comparison with the results of a similar study on two species of marine prawns and oil sardine, reported earlier.